1995
DOI: 10.1159/000292394
|View full text |Cite
|
Sign up to set email alerts
|

HPV DNA Positivity and Natural Killer Cell Activity in the Clinical Outcome of Mild Cervical Dysplasia: Integration between Virus and Immune System

Abstract: The objective was to examine the prevalence of human papillomavirus (HPV) DNA infection in mild cervical dysplasia and to evaluate longitudinally the persistence of HPV DNA positivity in an observational study, aiming at identifying the role of peripheral blood lymphocyte natural killer activity in the natural history of dysplastic disease. Twenty-three patients with histologically proven mild cervical dysplasia were selected. The HPV DNA positivity, determined by polymerase chain reaction, and cervical dyspla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…The same group has shown that decreased recognition of HPV-16 ϩ keratinocytes is re-lated to unresponsiveness of PBMC to immunostimulatory cytokines such as IL-2 and IFN-␣ (86). Other groups have also shown similar importance of NK activity in regression of SIL (54,134).…”
Section: School Of Medicine University Of California San Francisco mentioning
confidence: 64%
“…The same group has shown that decreased recognition of HPV-16 ϩ keratinocytes is re-lated to unresponsiveness of PBMC to immunostimulatory cytokines such as IL-2 and IFN-␣ (86). Other groups have also shown similar importance of NK activity in regression of SIL (54,134).…”
Section: School Of Medicine University Of California San Francisco mentioning
confidence: 64%
“…This underscores the importance of NK cells in early viral defense. In humans, NK cells may be important in infections with various viruses, including herpes simplex virus, EpsteinBarr virus, human cytomegalovirus, and human immunodeficiency virus (17,35). Recently, two studies have addressed the issue of a role for NK cells in the anti-HCV immune response, showing that engagement of CD81 on NK cells by the major envelope protein of HCV (HCV E2) leads to inhibition of NK cells (10,50).…”
Section: Discussionmentioning
confidence: 99%
“…RNA was isolated with the RNeasy system (Qiagen) in accordance with the instructions of the manufacturer. One microgram of RNA was incubated with oligo(dT) [12][13][14][15][16][17][18] primer (Roche), deoxynucleoside triphosphates (Gibco BRL), and 2 U of Moloney murine leukemia virus reverse transcriptase (RT; Gibco BRL) at 37°C for 1 h to generate cDNA. The cDNA was used as a template for PCR amplification of the gene products HLA-A (5Ј-GAC AGC GAC GCC GCG AGC CA-3Ј and 5Ј-GGC AGC GAC CAC AGC TCC AG-3Ј; 817 bp), HLA-B (5Ј-GAC AGC GAC GCC GCG AGT CC-3Ј and 5Ј-AGT AGC GAC CAC AGC TCC GA-3Ј; 798 bp), HLA-C (5Ј-GAG ATC ACA CTG ACC TGG CA-3Ј and 5Ј-GAA CAC AGT CAA TGT GGG G-3Ј; 630 bp), TAP1 (5Ј-ACG TCC ACC CTG AGT GAT TC-3Ј and 5Ј-AGC TTT TCC CTA AAC TTC TGG G-3Ј; 381 bp), TAP2 (5Ј-TAC CTG CTC ATA AGG AGG GTG C-3Ј and 5Ј-ATT GGG ATA TGC AAA GGA GAC G-3Ј; 311 bp), tapasin (5Ј-AGT TCA ACC CTT TCA GGA GGG CA-3Ј and 5Ј-GAA AGG CAG ACA GGA AAA GGC-3Ј; 385 bp), LMP2 (5Ј-TTG TGA TGG GTT CTG ATT CCC G-3Ј and 5Ј-CAG AGC AAT AGC GTC TGT GG-3Ј; 347 bp), LMP7 (5Ј-TCG CCT TCA AGT TCC AGC ATG G-3Ј and 5Ј-CCA ACC ATC TTC CTT CAT GTG G-3Ј; 241 bp), ␤-actin (5Ј-GTG GGG CGC CCC AGG CAC CA-3Ј and 5Ј-CTC CTT AAT GTC ACG CAC GAT TTC-3Ј; 484 bp), and p53 (5Ј-ACA CAA TGC AGG ATT CCT CC-3Ј and 5Ј-AAG CTC AAA ACT TTT AGC GCC-3Ј; 321 bp).…”
Section: Methodsmentioning
confidence: 99%
“…Although the association of HPV16 E6 and E7 expression levels with increased cell growth and eventually with cellular transformation is well recognised [12,13], the reason for localised epidermal hyperplasia in ·ACE6E7#19 mice is unknown. The association of expression of HPV16 E6 and E7 with hyperplasia and dysplasia in the cervix, and eventually with cervical cancer, and the association of cervical intra-epithelial neoplasia [14][15][16] and of skin disease in ·ACE6E7#19 mice with local inflammation suggest that further study of the role of the immune system in the localised hyperplastic skin pathology of ·ACE6E7#19 mice is warranted.…”
Section: Discussionmentioning
confidence: 99%